CHAOTIC RANDOMIZED SPACE VECTOR PULSE WIDTH MODULATION INTENDED FOR INDUCTION MOTOR DRIVES IN INDUSTRIAL APPLICATIONS: SVPWM for Industrial Motor Drives (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
In this industrial era, induction motor control plays a vital role, especially in speed control. Adjustment of speed is essential in all control strategies from the application perspective. There are different pulse width modulation methodologies to tune the speed and reduce harmonics. Among various pulse width modulation (PWM) strategies, space vector PWM (SVPWM) proves best for harmonic reduction in drive applications of variable frequency. SVPWM topology is modified by incorporating some randomness, generating switching pulses for the inverter, thereby controlling induction motor drives. A chaotic-based randomized algorithm is synthesized in primitive SVPWM and termed chaotic random SVPWM (CRSVPWM). It is proved from the results that the efficiency and performance are higher for chaotic randomized SVPWM induction drives than all conventional methods of PWM, having higher harmonics, lower modulation index, and less flexibility. CRSVPWM shows the advantages of better fundamental output voltage, more straightforward digital realization, improved harmonic performance, and extreme simplicity in vector selection. It is simulated through MATLAB 2021R, and hardware-based experimental validation was done using the Vivado design suite environment with Spartans-6 FPGA (XC6SLX9-2tqg144).
Keywords: Total harmonic distortion induction drives; Random pulse generation; Harmonic spread factor; Chaotic random space vector pulse width modulation